A New Approach to LCA Evaluation of Lamb Meat Production in Two Different Breeding Systems in Northern Italy - Geß, Andreas; Viola, Irene; Miretti, Silvia; Macchi, Elisabetta; Perona, Giovanni; Battaglini, Luca; Baratta, Mario (Frontiers in Veterinary Science, 2020)
Lamb meat production provides vital landscape-management and ecosystem services; however, ruminant farming produces a considerable share of the world’s greenhouse gas emissions. To measure and compare the advantages and disadvantages of the intensification of livestock farming, a integrative analysis was conducted in this study by combining environmental impact analysis and animal welfare assessment. This approach is the first of its kind and is the innovative aspect of this paper. The methodology of Life Cycle Assessment (LCA) entails the holistic analysis of various impact categories and the associated emission quantities of products, services and resources over their life cycle, including resource extraction and processing, production processes, transport, usage and the end of life. The outlines of LCA are standardized in DIN EN ISO 14040/14044. To assess the environmental impacts of the production of lamb meat in northern Italy, two case studies were undertaken, using the LCA software GaBi. The analysis is based on primary data from two sheep-breeding systems (semi-extensive and semi-intensive in alpine and continental bioregions, respectively) combined with inventory data from the GaBi database, and data from the literature. The assessment was conducted for the functional unit of 1 kg of lamb meat, and focuses on the impact categories global warming potential, acidification potential and eutrophication potential. For an overall evaluation of the supply chain, we have also considered a parameter indicating animal welfare, in keeping with consumer concerns, employing an analysis of chronic stress as shown by cortisol accumulation. The goal is to derive models and recommendations for an efficient, more sustainable use of resources without compromising animal welfare, meat quality and competitiveness. The aim of this study is to provide a standard for individualized sustainability analyses for European lamb production systems in the future. From the LCA perspective, the more intensive case-study farm showed a lower impact in global impact factors and a higher impact in local impact categories, in comparison with the more extensively run farm that was studied. From the animal welfare perspective, lower amounts of the stress hormone cortisol were found on the extensively managed case-study farm.